Newtonian analogue of force and motion of a free particle in the gravitational field of Kerr-de Sitter space-time - Singh T.; Srivastava R.S. (My University, 2025)
In the first part of the paper the Newtonian analogue of force for the Kerr-de Sitter metric has been investigated. To the first-order of approximation, a component of the force vector corresponds to the Newtonian gravitational force and a cosmic force arising due to the cosmological constant A. Int the higher order of approximation, the relativistic correction terms due to rotation and the presence of A are obtained. In the second part of the paper the motion of a freely-falling body has been investigated. It is found that plane orbits are not possible. Also a radial fall is not possible and there is a rotational drag on the particle which has no Newtonian analogue. © 1987 D. Reidel Publishing Company.